Enabling Open Architecture in Military Systems: A Systemic and Holistic Analysis - Raquel L. V. Radoman; Michael Henshaw; Melanie King; Tim Rabbets (Systems)
Military systems, with their extended lifecycles, face challenges such as managing obsolescence, adapting to evolving operational needs, and ensuring interoperability in System of Systems contexts. Open Architectures (OAs) have been pursued to address these issues by adopting widely recognized interface standards instead of proprietary solutions, enabling more flexible and cost-effective system modifications. However, establishing effective OA environments—encompassing technical, commercial, and organisational dimensions—remains complex, with much of the existing knowledge restricted to the practices of a few governments. This paper presents a comprehensive analysis of OA in military systems, employing systems thinking tools to examine this multifaceted concept. It integrates perspectives from government and industry, addressing the ‘what’, ‘why’, and ‘how’ of OA, and introduces a framework for identifying enabling actions. Key findings highlight that OA success depends on defining ‘open for whom’, ‘to what level of detail’, and ‘in which parts of the system’. Moreover, achieving an effective OA environment requires strategic investment, the active engagement of a Community of Practice, and maturity in the technical and legal domains. This study provides decision-makers at early stages of adoption with the necessary strategic understanding to support the customisation of OA transformation plans to suit unique contexts.